Los derechos fundamentales de la mujer frente a la violencia de género - Ramírez Muñoz, Sonia Aydee (Universidad de San Buenaventura - Cali, 2018)
Since December 4, 2008, Law 1257 of 2008, in which public policies against all forms of violence against women in Colombia have been issued, is now in force, regulations that are catapulted as the legal challenge for the Protection of the Fundamental Rights of Women victims of all forms of violence in the domestic, labor, public, educational, advertising media and in their relationships, among others; In view of the Political Constitution and the International Treaties and Conventions on Human Rights ratified by Colombia, which entails visibilizing and recognizing that the continuous physical, emotional, and life-threatening aggression against Women is of great importance within the fabric Colombian and international social movements, since the different forms of violence affect the dignity, life and integrity of women in many different ways, nullifying their Fundamental Rights.